Foliar Zn Application Increases Zn Content in Biofortified Potato - Shirley Zevallos; Elisa Salas; Pedro Gutierrez; Gabriela Burgos; Bert De Boeck; Thiago Mendes; Hugo Campos; Hannele Lindqvist-Kreuze (Agriculture)
Given the widespread micronutrient deficiencies in vulnerable populations, crop biofortification has been proposed as a solution to increase nutrient concentrations. This study aimed to determine the effect of combining biofortification strategies on the agronomic characteristics and nutritional composition of potato. The effect of foliar fertilization (FF) with zinc (Zn) on five potato genotypes (G): four biofortified clones developed through conventional breeding with different Zn levels (high, medium, and low in Zn, and one high in Fe and Zn) and a commercial variety (‘Yungay’) were evaluated. At harvest, the number of tubers per plant, the weight of tubers per plant, and the average tuber weight were evaluated as yield components, and tuber samples were collected for micronutrient determination. For yield components, the analysis with linear mixed models showed no significant G × D interaction effects, but highly significant differences were observed among G. The Zn concentration in tubers showed a highly significant effect in the G × D interaction. The simple effects analysis showed that biofortified genotypes responded to FF with Zn by significantly increasing the tuber Zn concentrations by an average of 43% (range 28–61%), despite growing in alkaline soils. In contrast, the ‘Yungay’ variety showed a 6% increase. Clones biofortified through conventional genetic improvement responded better to agronomic FF with Zn compared to the non-biofortified commercial variety, demonstrating that both are synergistic strategies that can achieve a significant increase in Zn concentrations in tubers. The result of this study might be used to further biofortification efforts and decrease nutritional deficiencies.